Floristic composition and edaphic relationships in ferruginous campo rupestre reference ecosystems - Fernandes, G. Wilson; Ramos, Letícia; Paiva, Dario C.; Cunha-Blum, Jéssica; Gomes, Vanessa Matos; Negreiros, Daniel (Journal of mountain science, 2024)
Land use change and occupation have led to modifications in the environment causing loss of biodiversity and ecosystem services throughout the planet. Some environments with high economic relevance, such as the ferruginous campo rupestre (rupestrian grassland known as Canga in Brazil), are even more susceptible to severe impacts due to their extreme habitat conditions and low resilience. The determination of reference ecosystems based on the intrinsic characteristics of the ecosystem is essential for conservation as well as to the implementation of ecological restoration. We proposed the reference ecosystem of the three main types of habitats of the ferruginous campo rupestre based on their floristic composition. We described the floristic composition of each habitat and evaluated the physicochemical properties of the soils and the relationship between plants and soils. All three habitats showed high diversity of plant species and many endemic species, such as Chamaecrista choriophylla, Cuphea pseudovaccinium, Lychnophora pinaster , and Vellozia subalata. The distribution of vegetation was strongly related with the edaphic characteristics, with a set of species more adapted to high concentration of base saturation, fine sand, organic carbon, and iron, while another set of species succeeded in more acidic soils with higher S and silt concentration. We provide support for the contention that the ferruginous campo rupestre is a mosaic of different habitats shaped by intrinsic local conditions. Failure to recognize the floristic composition of each particular habitat can lead to inappropriate restoration, increased habitat homogenization and increased loss of biodiversity and ecosystem services. This study also advances the knowledge base for building the reference ecosystem for the different types of ferruginous campo rupestre habitats, as well as a key database for highlighting those species contribute most to community assembly in this diverse and threatened tropical mountain ecosystem.